EFL Students’ Learning Styles on Basic Reading in Higher Education - Yulmiati, Yulmiati (Universitas PGRI Sumatera Barat, 2024)
This research aims at finding students’ learning styles on Basic Reading. Difficulties that arise at learning Basic Reading are often due to differences in learning styles. It has been proposed that the lecturers should assess the learning styles of their students and adapt their classroom activities and assessment to best suit of student’s learning style. The data were collected in form of a survey using questionnaire. The samples were 55 students who enrolled in the first semester of higher education that selected randomly. It was found that in perceptual learning styles the students preferred having a visual style (3.79), followed by auditory (3.48), kinesthetic (3.47), reading/writing style (3.42), and tactile (3.40). Meanwhile, in sociological learning styles, the students preferred to study in a group (3.73) and an individual learning style (3.29). The findings show that the awareness on students’ preference in learning styles can help the lectures to design learning activities and task to them. By considering the students’ learning styles, we can achieve better pedagogical outcomes in Basic Reading classroom later.